SEJARAH MASUKNYA KEBUDAYAAN TIONGHOA DIKECAMATAN SINABOI KABUPATEN ROKAN HILIR - Rosmaliza '; Ridwan Melay Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to knowing history influx of chinese culture in the sub district Sinaboi Rokan Downstream. Chinese community in the district Sinaboi is of the tribe Hokkien clan has ang. Tribes Hokkien are peoples cleverness trading already attached insid every person Hokkien tribe. The chinese people out of the country caused because economic demands and political force they are out to get out of he area origin and look for new areas decent place to stay. Purpose of this research is (a) to determine the origin of the ancestors chinese (b) to know the culture that was brought by the chinese ethnic in the subdistrict Sinaboi Rokan Hilir (c) to know mixing cultures chinese community by cummunity the local subdistrict are Sinaboi Regency Rokan downstream (d) to know livellihood system community in the subdistrict Sinaboi Rokan Hilir (e) to know the response of local communities to the culture of the people in the district chinese Sinaboi Rokan downstreamdistricts. This research method is qualitative descriptive. Where this research is subdistrict Sinaboi Rokan downstream. This study time for 2 weeks. Data collection techniques in this study include three techniques, namely observation techniques, interview techniques , documentation techniques, and literature techiques. The results of thisstudy are based on the obsevation, interviews aimed to know the history of the inclusion of culture in the district chinese Sinaboi Regency Rokan Downstream. Keywords: History Influx Of Chinese Culture